The Crucial Role of Islamic Religious Education in Shaping Children's Character: Psychological and Spiritual Review - Irpan, Irpan; Sain, Zohaib Hassan (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The significance of Islamic religious education in shaping children's character is paramount in contemporary society. This study aims to explore the transformative impact of Islamic education on children's moral and spiritual development, utilizing a comprehensive analysis that integrates psychological and spiritual perspectives. A mixed-method approach combining literature review and empirical research elucidates how Islamic education fosters moral reasoning, empathy, and self-regulation among children while nurturing a profound spiritual connection and inner transformation. Here are the steps: 1) Literature Review: Start by compiling a comprehensive literature review about the importance of Islamic religious education in forming children's character. Please focus on the psychological theories that support this argument and their relationship to aspects of spirituality. 2) Empirical Research: conducting empirical research to support the claim. Use appropriate research methods such as surveys, interviews, or observations to collect relevant data from respondents from various backgrounds and ages. The findings underscore the holistic nature of Islamic education in equipping children with the ethical fortitude, emotional resilience, and spiritual consciousness necessary to navigate life's challenges with integrity and purpose. Our research findings demonstrate how Islamic education fosters moral reasoning, empathy, and self-regulation among children while nurturing a deep sense of spiritual connection and inner transformation. By integrating psychological insights with spiritual teachings, Islamic education offers a holistic approach to character development, equipping children with the ethical fortitude, emotional resilience, and spiritual consciousness necessary to navigate life's challenges with integrity and purpose.